Cannabinoid-Induced Stereoselective Inhibition of R-S-Oxazepam Glucuronidation: Cannabinoid-Oxazepam Drug Interactions - Keti Bardhi; Shelby Coates; Gang Chen; Philip Lazarus (MDPI AG, 2024)
Benzodiazepines (BZDs) such as oxazepam are commonly prescribed depressant drugs known for their anxiolytic, hypnotic, muscle relaxant, and anticonvulsant effects and are frequently used in conjunction with other illicit drugs including cannabis. Oxazepam is metabolized in an enantiomeric-specific manner by glucuronidation, with S-oxazepam metabolized primarily by UGT2B15 and R-oxazepam glucuronidation mediated by both UGT 1A9 and 2B7. The goal of the present study was to evaluate the potential inhibitory effects of major cannabinoids, Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD), and major THC metabolites, 11-hydroxy-Δ9-tetrahydrocannabinol (11-OH-THC) and 11-nor-9-carboxy-Δ9-tetrahydrocannabinol (11-COOH-THC), on the UGT-mediated metabolism of R- and S-oxazepam. The cannabinoids and metabolites were screened as inhibitors of R- and S-oxazepam glucuronidation in microsomes isolated from HEK293 cells overexpressing individual UGT enzymes (rUGTs). The IC50 values were determined in human liver microsomes (HLM), human kidney microsomes (HKM), and rUGTs and utilized to estimate the nonspecific, binding-corrected Ki (Ki,u) values and predict the area under the concentration-time curve ratio (AUCR). The estimated Ki,u values observed in HLM for S- and R-oxazepam glucuronidation by CBD, 11-OH-THC, and THC were in the micromolar range (0.82 to 3.7 µM), with the Ki,u values observed for R-oxazepam glucuronidation approximately 2- to 5-fold lower as compared to those observed for S-oxazepam glucuronidation. The mechanistic static modeling predicted a potential clinically significant interaction between oral THC and CBD with oxazepam, with the AUCR values ranging from 1.25 to 3.45. These data suggest a pharmacokinetic drug-drug interaction when major cannabinoids like CBD or THC and oxazepam are concurrently administered.